Computational Thinking for All: What Does It Mean for Teacher Education in Brazil? - Pontual Falcão, Taciana (Anais do Simpósio Brasileiro de Educação em Computação (EDUCOMP); 2021: Anais do Simpósio Brasileiro de Educação em ComputaçãoDO - 10.5753/educomp.2021.14505, 2021)
Integrating Computational Thinking (CT) and Computer Science (CS) concepts to childrens education is a hot topic nowadays. However, most research around this topic focuses on the students, how they learn and what they need to learn. Much less work has been done on the teachers needs to acquire and develop the necessary CT skills and knowledge to be teaching these students. Reflecting a general trend towards autonomous learning, many CT resources for educators are available, such as online courses for building capacity as well as activities and tools to be used in lessons. Nevertheless, little change is perceived in Brazilian schools, and knowledge about CT among schoolteachers is still incipient, indicating that, for teachers to integrate CT within their disciplines, in-service (and mostly autonomous) development might not be sufficient. Meanwhile, faculty from teacher education undergraduate programs have been mostly unresponsive to these new demands related to CT. In fact, instructors themselves need to develop this new competence, as they are not familiar with the concept of CT or how to apply it. Very particular to the Brazilian context, CS teacher education programs (Licenciatura em Computação) could be a key to solve this puzzle, as both faculty and student teachers are dealing with CS Education and CT. However, the CS student teachers remain isolated and often ignored by national policies, while most investment is made on in-service development for schoolteachers from all other disciplines. This paper presents CT research in Brazil related to teacher education, resources for in-service training, the potential contribution of the CS teacher education programs, and, within this context, discusses which directions could be followed to inform national policies and curricula adaptations in higher education institutions. In our opinion, more attention must be given to developing CT in higher education institutions, including both facultys CT abilities and knowledge, and curriculum redesign.